Rebranding Koperasi sebagai Strategi Meningkatkan Kinerja dan Daya Tarik Koperasi Berdasarkan Indikator Pemeringkatan Koperasi di Indonesia - Iwan Mulyana; Tryiis ARR; Endang Wahyuningsih (J-Coop : Journal of Co-operative, 2026)
Cooperatives constitute a cornerstone of the national economy, grounded in the principles of economic democracy and oriented toward enhancing members’ welfare. Nevertheless, the development of cooperatives in Indonesia continues to face various structural and managerial challenges, as reflected in their low rankings and levels of financial and organizational health. Furthermore, challenges related to member regeneration and the declining interest of Millennials and Generation Z have intensified the urgency for renewing cooperative development strategies. This study aims to analyze the development of cooperatives in Indonesia based on cooperative ranking indicators and to examine the role of cooperative rebranding as a strategy to improve performance and attractiveness. This research employs a qualitative approach using a literature review method, drawing on scientific journals, books, and reports from relevant national and international institutions published over the last ten years. The findings indicate that cooperative challenges encompass institutional, managerial, business, financial, and member benefit aspects. Cooperative rebranding is viewed as a comprehensive strategy that extends beyond changes in visual identity to include transformations in governance, services, and organizational values. This study concludes that integrating cooperative rebranding with cooperative ranking indicators can serve as a strategic approach to enhancing the sustainability and competitiveness of cooperatives in Indonesia.